A Decision Model for Service-Oriented Manufacturing Firms Based on The Product Lifecycle - He, Jinzhe; Chen, Xu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
Facing saturated product markets, manufacturers are transforming by embedding services across the product lifecycle. This study develops a lifecycle-based game-theoretic model to determine the optimal product price, service price, and service quality for service-oriented manufacturers. Using backward induction, the model identifies optimal decisions under distinct profitability scenarios and examines the influence of key market factors through sensitivity analysis. Findings reveal that the trade-off between product and service profits is shaped by the warranty period and the ratio of consumer sensitivity to product price versus service utility. Accordingly, three profitability regimes—product-dominated, mixed, and service-dominated—are defined. A shorter warranty or higher sensitivity ratio promotes high service quality, whereas a longer warranty or lower ratio favors lower quality. Extending the model to include partial in-warranty service charging shows that charging a fraction of service fees maintains profitability while supporting extended warranty coverage, offering actionable insights for lifecycle-based decision-making.